DETERMINING CRITERIA WEIGHTS FOR VEHICLE TRACKING SYSTEM SELECTION USING PIPRECIA-S - Aytekin, Ahmet (Journal of process management and new technologies, 2022)
Vehicle tracking systems are generally used to determine the location of vehicles, monitor them, and guide them when appropriate. This study aims to define the criteria that logistics companies consider when selecting a vehicle tracking system, as well as the relative importance of these criteria. PIPRECIA-S, a multi-criteria decision analysis method, was used in this context. According to the analysis results, the most important criterion in the selection of a vehicle tracking system is real-time tracking of the vehicle's location. When it comes to selecting a vehicle tracking system, logistics firms should prioritize instant vehicle tracking, compliance with local rules, compatibility with new technologies and software, quality certification, and compatibility with external systems-devices over other criteria. Other important criteria to consider when selecting a vehicle tracking system are system maintenance and technical support, providing statistical data collection and effective reporting, allowing the vehicle to be diverted, comprehension, simplicity of implementation and visual geo-information presentation for users, design and quality of hardware, system cost, communication infrastructure, and reducing the operating costs of companies. Also, when developing vehicle tracking systems, system developers can prioritize the aforementioned criteria.